ACTR-34. INTEGRATED CLINICAL EXPERIENCE WITH ONC201 IN PREVIOUSLY-TREATED H3 K27M-MUTANT GLIOMA PATIENTS. (5th November 2018) - Chi, Andrew; Arrillaga-Romany, Isabel; Gardner, Sharon; Wen, Patrick; Batchelor, Tracy; Hall, Matthew; Odia, Yazmin; Khatua, Soumen; Zaky, Wafik; McGovern, Susan; Harrison, Rebecca; de Groot, John; et al.
Abstract: BACKGROUND: H3 K27M-mutant gliomas have a dismal clinical prognosis and no proven curative therapy. We report the updated clinical experience with ONC201, the first cancer-specific DRD2 antagonist, in adult and pediatric H3 K27M-mutant gliomas. METHODS: As of May 28, 2018, 26 patients with H3 K27M-mutant glioma have been treated with ONC201: 9 pediatric (<18 years old) and 17 adult patients (>18 years old). Twelve patients had recurrent disease and 14 had previously-treated stable disease prior to initiating ONC201. Patients had 1–4 prior lines of therapy and all received prior radiation. Ten adult patients were enrolled on clinical trials and the other 16 were on compassionate use. ONC201 was orally administered at 625 mg to adults and scaled by body weight for pediatric patients. All patients, except one, were dosed weekly. RESULTS: Fourteen of 26 patients (54%) remain progression-free on ONC201 with a median follow up of 3.6 (range 1.6–24.5) months. No dose modifications or discontinuation due to toxicity have occurred. Among the 12 adult patients with recurrent disease who received single agent ONC201, the estimated PFS6 is 36.5%. Seven patients have experienced radiographic and/or clinical benefit (neurological stabilization or improvement). Among the 5 adults with recurrent thalamic glioma, three have experienced durable complete regression of their thalamic tumors, including the first H3 K27M-mutant glioma patient treated with ONC201 who has experienced 96% regression of her recurrent disease and continues single agent ONC201 for >2 years. Two DIPG pediatric patients who initiated single agent ONC201 6–8 weeks after radiation have experienced radiographic and neurological improvements and exhibited PFS of >13 months from diagnosis. CONCLUSIONS: Emerging clinical data suggest that ONC201 exhibits clinical activity for some patients with H3 K27M-mutant glioma.